PROSEDUR PENYALURAN KREDIT USAHA RAKYAT (KUR) PADA PT.BANK RAKYAT INDONESIA (PERSERO) - Wayan Arsane; Nyoman Ari Surya Darmawan (Jurnal Widya Akuntansi dan Keuangan, 2021)
This research aims to know the procedures of the people's Business Credit distribution (KUR) at PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Goris. The Data used is qualitative in the form of KUR file, KUR analysis, and the organizational structure of PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Goris and its duties. The subject of this research is PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Goris, and the object of this research is KUR dispensing procedure. Data collection methods are conducted by interview techniques, observations and documentation. The Data obtained is analyzed by using a qualitative descriptive. The results of this study showed that the channeling procedure of Usaha Rakyat at PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Goris has been done well by BRI Unit Goris.